Penerapan Manajemen Risiko untuk Meminimalisir Non Performing Financing pada Bank Muamalat KCP Darmo Surabaya - Desiyanti, Nur Alfiyah; Wigati, Sri (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This research aims to analyze the application of risk management in order to minimize non- performing financing (NPF) at Bank Muamalat KCP Darmo. Bank Muamalat as a sharia bank is committed to maintaining the quality of its financing portfolio by minimizing the risk of problematic financing. The research method used is qualitative with a case study approach, involving interviews with risk managers, document analysis and direct observation in the field. The research results show that Bank Muamalat KCP Darmo has implemented various risk management strategies, including risk identification, risk assessment, risk control and regular risk monitoring. The implementation of risk management has helped banks reduce NPF risk by increasing understanding of the risks faced and implementing effective prevention and mitigation measures. However, the research also highlights several challenges faced by Bank Muamalat KCP Darmo in implementing risk management. It is hoped that the results of this research can contribute to the development of more effective risk management practices in the Islamic banking industry.